Determining Key Material Matters In Sustainability Reporting: Does Industry Types Matter? - Mat Husin, Norhayati, Alrazi, Bakhtiar, Mohd Salleh, Sharina, Abdullah, Nurul Wahida2 (International Journal of Advanced Science and Technology, 2020)
With the additional demand for companies to also provide sustainability reports, corporate reporting has becoming overwhelming in quantity and do not necessary help stakeholders understand the business performance. This lead to the need for companies to conduct a materiality assessment for their sustainability report. Malaysia, in particular, has introduced a revised2018 Sustainability Reporting Guide, which include a materiality matrix that helps companies prioritize their material sustainability matters. Despite the growing importance of materiality assessment in sustainability reporting, little is known on the extent of materiality assessment practice among Malaysian companies. This study aims to provide a preliminary analysis on key matters that are commonly considered as material by top 50 Malaysian public listed companies and examine whether industry types play a significant role in differentiating the amount/category of key material matters identified. By content analyzing the top 50 companies’ 2018 corporate report ranging from annual reports to stand-alone reports, the findings show each company has identified, on average, 16 matters that are considered as key to their sustainability. The findings also show the most prioritize matter in the assessment is under the category ‘Social’ with each company identified, on average, 6 social related matters. Based on the Kruskall Wallis test, there seem to be no significant difference, in the total number of key material matters identified, between companies from different types of industry. However, a much detail analysis on category of key material matters show there is a significant difference between companies from different types of industry when it comes to matters under the category ‘Economic’. The other three categories i.e. environment, governance and social do not have any significant difference.Findings from this study areconsidered as crucial as it provide initial understanding on Malaysian companies’ behavior in determining matters that is considered as material to their sustainability.